A Niemann-Pick Disease Type C2 with Severe Pulmonary Involvement and Limited Therapeutic Options: A Case Report - Abdullah Al-Shamrani; Khalid Al-Shamrani; Ahmed Bin Mahfoudh; Ahmed Sarar Mohamed; Sarar Mohamed (MDPI AG, 2022)
Niemann-Pick disease type C (NPC) is an autosomal recessive lipid storage disorder. There are two types, NPC1, which is the predominant form (95%), and the rare NPC2, which represents less than 5% of the reported cases. Niemann-Pick disease type C2 usually presents with respiratory symptoms, cholestasis, neurological impairment, and hepatosplenomegaly. Case report: Here, we report a 3-year-old boy who presented to our hospital with exacerbation of chronic lung disease requiring invasive ventilatory support. He was previously diagnosed with interstitial lung disease. His parents used to instill olive oil in his nose (a few drops in each nostril daily for several months) to treat frequent nasal bleeding. A detailed history revealed prolonged neonatal jaundice for four months, with hepatosplenomegaly. In his second year, generalized hypotonia and delayed psychomotor development were observed. Upon presentation to our institute, chest CT showed evidence of intraparenchymal fat; therefore, lipoid pneumonia and lipid storage disease were suspected. The bronchoalveolar lavage results suggested pulmonary alveolar proteinosis (PAP). Whole-exome sequencing (WES) revealed a class one homozygous pathogenic variant in the NPC2 gene. Our patient faced a range of difficulties, including prolonged mechanical ventilation and diagnostic and therapeutic challenges. Conclusion: Niemann-Pick disease type C2 is a progressive and lethal condition that requires a high index of suspicion to pinpoint the diagnosis. Gene study remains the method of choice to confirm the diagnosis. There are limited choices of therapeutic interventions; therefore, genetic counseling and the prevention of recurrence should be the ultimate goal for affected families.